2018
DOI: 10.3382/ps/pex385
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with curcuminoids and tuna oil influenced skin yellowness, carcass composition, oxidation status, and meat fatty acids of slow-growing chickens

Abstract: The present study aimed to determine the effects of dietary curcuminoids combined with tuna oil on the growth performance, meat quality, thiobarbituric acid reactive substances (TBARS) values in the plasma and raw meat, and fatty acid profile of chicken meat. A total of 480 21-day-old mixed-sex slow-growing chickens was assigned to a completely randomized design model with 6 treatments and 4 replicates (pens) per treatment. The basal diet based on corn-soybean and 4% tuna oil was used as the negative control. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
2
16
0
1
Order By: Relevance
“…It was observed that the total omega-3 and omega-3/omega-6 rates were affected by the addition of turmeric at a significant level (P<0.05) and these rates reached peak values at 6 g/kg level. Similarly, these findings, Hang et al (2018) reported that supplementation of curcumin (20 mg/kg curcuminoids) to broiler diets significantly increased the linoleic acid and total n-6 PUFA contents in the breast meats. The enzyme Δ-6 desaturase promotes the desaturation of linoleic acid into arachidonic acid and α-linolenic into docosohexaenoic acid (DHA) and eicosapentaenoic acids (EPA) (Pereira et al 2011).…”
Section: Fatty Acid Compositionsupporting
confidence: 59%
See 1 more Smart Citation
“…It was observed that the total omega-3 and omega-3/omega-6 rates were affected by the addition of turmeric at a significant level (P<0.05) and these rates reached peak values at 6 g/kg level. Similarly, these findings, Hang et al (2018) reported that supplementation of curcumin (20 mg/kg curcuminoids) to broiler diets significantly increased the linoleic acid and total n-6 PUFA contents in the breast meats. The enzyme Δ-6 desaturase promotes the desaturation of linoleic acid into arachidonic acid and α-linolenic into docosohexaenoic acid (DHA) and eicosapentaenoic acids (EPA) (Pereira et al 2011).…”
Section: Fatty Acid Compositionsupporting
confidence: 59%
“…Salah et al (2019) reported that supplementation of 100 mg curcumin /kg broiler diet significantly decreased SFA contents in the breast meat. However, Hang et al (2018) reported that no significant changes in the SFA contents of breast and thigh meats of chickens were fed curcuminoids-supplemented diets.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…Similarly, Nouzarian et al [ 39 ] reported a significant decrease abdominal fat in broilers fed diets supplemented with turmeric powder (38.28 mg/kg curcumin content). Other researchers suggested that the different levels of curcuminoids in the broiler diets significantly reduced the percentage of abdominal fat [ 36 ]. Rajput et al [ 22 ] did not report significant effects on the percentage of abdominal fat, when added up to 150 mg/kg pure curcumin in the broiler diets.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported by Daneshyar et al [ 44 ], who stated that the addition of curcuma powder (0.75%) to broiler diets decreased the levels of saturated FAs in thigh muscles. Meanwhile, others suggested that curcuminoids supplementation did not alter the levels of saturated FAs in the breast and thigh muscles of Korat chickens [ 36 ]. Herein, the current study demonstrated the ability of dietary curcumin to restore the levels of MUFAs and PUFAs in the breast and thigh muscles of heat-stressed broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados en el contenido lipídico de la carne podrían deberse al contenido de altas cantidades de polifenoles, flavonoides y fibra del ajo, arándano y cúrcuma que pueden mediar un aumento en la excreción de ácidos biliares y la capacidad de la fibra para disminuir el contenido lipídico (Kim et al, 2009). En particular, los niveles de MDA en los tratamientos ARP y CCP fueron más bajos que en los otros tratamientos, resultados concordantes con los encontrados por Hang et al (2018), quienes redujeron los niveles de TBARS en carne de pollo con curcuminoides, atribuyendo estos bajos niveles a la posible ruptura significativa de los hidroperóxidos inmediatamente de producido el sacrificio de las aves.…”
Section: Contenido Lipídico Y Estado Antioxidante De La Carneunclassified